Perancangan Sistem Informasi Wisata Air Di Daerah Istimewa Yogyakarta Berbasis Web - Fani Novianti Rizaniar - AMIK BSI Yogyakarta; Sardiarinto - AMIK BSI Purwokerto (Universitas Bina Sarana Informatika, 2015)
Abstract Indonesia is one of the countries that have natural resources that ought to be proud of, one of which is located in the tourist area of Yogyakarta Special Region. Yogyakarta is a famous tourist spot in the area of domestic and foreign. In this province there are four districts and one municipality with many sights and especially for water tourism, based on visitor data obtained from the Department of Tourism Yogyakarta, water tourism has the most visitors in comparison with other tourist. However, there is still a lack of information about places of tourist attraction that is very interesting. From these data we decided to design a Water-Based Travel Information Openness Web. Of research and data collection we have a lot of information and data. Of the three methods of research, observation, interview and literature as well as a waterfall method of software development has got everything needed to build the system. This system can be used as a tool in the search for resources and establish the purpose of promotion to increase the number of tourists both domestic or overseas. Keywords: Website,Information Systems, Water Travel.